A multi-model study of impacts of climate change on surface ozone in Europe - J. Langner; M. Engardt; A. Baklanov; J. H. Christensen; M. Gauss; C. Geels; G. B. Hedegaard; R. Nuterman; D. Simpson; J. Soares; M. Sofiev; P. Wind; et al. (Atmospheric Chemistry and Physics, 2012)
The impact of climate change on surface ozone over Europe was studied using four offline regional chemistry transport models (CTMs) and one online regional integrated climate-chemistry model (CCM), driven by the same global projection of future climate under the SRES A1B scenario. Anthropogenic emissions of ozone precursors from RCP4.5 for year 2000 were used for simulations of both present and future periods in order to isolate the impact of climate change and to assess the robustness of the results across the different models. The sensitivity of the simulated surface ozone to changes in climate between the periods 2000–2009 and 2040–2049 differs by a factor of two between the models, but the general pattern of change with an increase in southern Europe is similar across different models. Emissions of isoprene differ substantially between different CTMs ranging from 1.6 to 8.0 Tg yr−1 for the current climate, partly due to differences in horizontal resolution of meteorological input data. Also the simulated change in total isoprene emissions varies substantially across models explaining part of the different climate response on surface ozone. Ensemble mean changes in summer mean ozone and mean of daily maximum ozone are close to 1 ppb(v) in parts of the land area in southern Europe. Corresponding changes of 95-percentiles of hourly ozone are close to 2 ppb(v) in the same region. In northern Europe ensemble mean for mean and daily maximum show negative changes while there are no negative changes for the higher percentiles indicating that climate impacts on O3 could be especially important in connection with extreme summer events.